“Caught in the Loop": How Fear of Missing Out and Neuroticism Drive Problematic Social Media Use in Young Adults - Sovi Septania; Avin Fadilla Helmi; Haidar Buldan Thontowi (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Nowadays, social media is the most popular platform on the internet. Along with its role in society, it also has a negative effect brought on by problematic use. Young adults, as the first generation to grow up in a highly digitized society, become normative in using social media. The more intensely young adults use social media, the higher their potential exposure to problematic social media use (PSMU). The abundance of information leads us to easily find out information about other people which in turn causes anxiety in itself. This study aims to empirically analyze the contribution of fear of missing out (FOMO) and neuroticism to PSMU and to describe the psychological dynamic of PSMU in young adults. A convergent parallel mixed-methods design was used for this study, with 210 participants selected using the purposive sampling technique. The two data sets were then integrated using the joint display and interpreted as either convergent or divergent results. The findings revealed that FoMO and neuroticism had a positive correlation with PSMU. Simultaneously, FOMO and neuroticism contributed 30.9% to PSMU. There were four themes that evolved as the result of thematic analysis: (1) pleasant experiences, (2) tolerance for the duration of use, (3) perceived negative effects, and (4) responses to the reduction of usage duration to a certain extent. The research findings suggest that self-awareness of social media’s negative impacts plays a critical role in preventing problematic social media use from escalating into worse behavior. Further implication is discussed.